SUGAR Model-Assisted Analysis of Carbon Allocation and Transformation in Tomato Fruit Under Different Water Along With Potassium Conditions - Luo, Anrong; Kang, Shaozhong; Chen, Jinliang (Frontiers in Plant Science, 2020)
Carbohydrate concentration is closely related to water and mineral nutrition in fruits; water stress and minerals alter the assimilation, operation and distribution of carbohydrates, thereby affecting fruit quality. In order to explore the dynamic effects of different water and potassium conditions on photoassimilates in fruit growth and development, we analyzed the variation of carbon during the whole growth stage based on relevant experimental data and the SUGAR model. Also, we quantitatively studied the distribution of photoassimilates such as structural carbohydrates, soluble sugars, and starch in fruit and their response to water and potassium supply. Firstly, the results showed that the carbon allocation and transformation dynamically changed during the whole growth stage; in fact, the variation trend of carbon was the same under different water and potassium conditions, and the main carbon allocation at the early stages was due to the accumulation of starch and other compounds. The relative rate of carbon conversion of soluble sugars to other compounds (k3) and that of soluble sugars to starch (k5m) dropped during the whole growth stage. Also, the carbon in the form of starch was converted to soluble sugars and carbon was mainly distributed as soluble sugars at maturity; mainly owing to sugar accumulation, k3(t) and k5m(t) approached 0 at the end of the growth stage. Secondly, it was found that applying potassium can significantly increase the carbon allocation and transformation into soluble sugars during the whole growth stage, especially there was a remarkable significant difference between potassium and without potassium application treatments at the fruit maturation stage; while the carbon conversion coefficients k3(t) and k5m(t) were reduced accompanied by fruit development. Finally, we concluded that water deficit can regulate the carbon allocation of fruits and significantly increase the carbon content of fruits in the form of starch and soluble sugars; therefore, it reduced the carbon content of the other compounds in the fruit and improved the fruit quality.